1981
DOI: 10.1203/00006450-198111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cerebral Blood Flow in Term Infants with Hypoxic-Ischemic Encephalopathy

Abstract: Summary MATERIALS AND METHODSEstimated cerebral blood flow (eCBF) was measured sequenSeven asphyxiated infants showing evidence of HIE and seven tially in seven term infants with evidence of hypoxic-ischemic normal-term infants were studied. ,411 infants in the control group encephalopathy (HIE) and compared with that of normal-term were selected from the normal newborn nurseries of the Royal infants. The eCBF was determined by a noninvasive method Alexandra Hospital and were found to be completely normal upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…The low CBF values in our patients could be consistent with the values described in the literature which succeeded the initial phase of hy- peremia [14] after perinatal asphyxia. The study of Shakaran et al [14] demonstrated low blood flow values up to 4 days after a hypoxic-ischemic event. However, these data are in contrast to Doppler studies demonstrating increased cerebral blood flow velocities up to 4 days after the hypoxic injury [15,16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The low CBF values in our patients could be consistent with the values described in the literature which succeeded the initial phase of hy- peremia [14] after perinatal asphyxia. The study of Shakaran et al [14] demonstrated low blood flow values up to 4 days after a hypoxic-ischemic event. However, these data are in contrast to Doppler studies demonstrating increased cerebral blood flow velocities up to 4 days after the hypoxic injury [15,16].…”
Section: Discussionsupporting
confidence: 80%
“…But their study included ventilated neonates with severe respiratory distress syndrome or persistent pulmonary hypertension which may lead to low CBF values [2,13] even in the absence of a neurological disturbance [7]. The low CBF values in our patients could be consistent with the values described in the literature which succeeded the initial phase of hy- peremia [14] after perinatal asphyxia. The study of Shakaran et al [14] demonstrated low blood flow values up to 4 days after a hypoxic-ischemic event.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, studies with arterial oxygen saturations as low as 20-25% have demonstrated that the oxygenation and function of the heart, brain, adrenal glands, and diaphragm appear to be preserved because of a redistribution of the circulation with increased blood flows to these organs (12,14,30). Thus, hypoxemia does not reduce blood flow or oxygenation in the heart, brain, adrenal glands, or diaphragm as would be expected if hypoxemia could explain the necropsy data demonstrating ischemic/hypoxic injury after birth asphyxia (5,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 79%
“…Asphyxia also is frequently associated with metabolic disturbances such as hypoxemia and acidemia (6,7). As clinical and necropsy data from asphyxiated newborns have suggested that the organ injury of birth asphyxia is consistent with perinatal ischemia and/or tissue hypoxia (5,(8)(9)(10), experimental studies have focused on the relationship between the metabolic abnormalities that occur during asphyxia and total cardiac output as well as regional organ blood flows. Many studies have demonstrated that neonatal and fetal ovine hypoxemia results in reductions in renal, gastrointestinal, splenic, and hepatic blood flows (11-13).…”
mentioning
confidence: 99%
“…The infants in groups 2 and 3 suffered varying degrees of hypoxic-ischemic encephalopathy and its complications. The latter two groups had a history suggestive of fetal distress including meconium staining, fetal heart rate abnormalities, severe antepartum hemorrhage or a complicated delivery including breech extraction, difficult forceps extraction, failed forceps and/or cesarean sec tion for prolonged labor or fetal distress [9]; immediate neonatal asphyxia as evidenced by the need for immediate intubation and resuscitation; evidence of neurologic dysfunction as shown by seizures, marked abnormalities in behavioral state, posture, tone, motility and reflexes [9], Electroencephalograms and computerized tomographic scans were done on all infants and showed abnormalities compatible with hypoxic-ischemic encephalopathy. Group 2 differed from group 3 in the following manner; all infants in group 2 showed evidence of pulmonary complications such as meconium aspiration and persistent fetal circulation.…”
Section: Methodsmentioning
confidence: 99%